Employment and Income Insecurity Experienced by Low-to-Moderate-Income Latinas During the COVID-19 Pandemic - Stephanie Brito-Yates; Luisa Blanco; Grace Vasquez; Jocelyn Sandoval; Julie Friedman; Angel Ramos; Helen Ramos; Christine Tran; Gabrielle A. Pascua; Ryan McKenzie; Sophie Viray; Janet Pregler (Health Equity)
Purpose: Research has established interconnections between financial strain and health outcomes. The COVID-19 pandemic disproportionately affected low-to-moderate-income (LMI) Latinas. The added stress may have strained the mental and physical health of LMI Latinas. Understanding the impact of the pandemic on financial and health status among Latinas offers important insights into ongoing pandemic recovery efforts to reduce health and financial disparities. Methods: This study employed community-based participatory qualitative and quantitative research methods to examine the experiences of Latinas residing in Los Angeles (LA) County in relation to their health and financial challenges. Focus groups were conducted among LMI Spanish-speaking Latinas, who are residing or employed on the west side of LA County. Study participants were members of Building Skills Partnership, which is a trade association training union workers. Results: Participants identified concerns that pandemic closures, reduction in work hours, unemployment, insurance loss, and childcare loss are attributed to financial hardship. Consequently, participants expressed that their ability to manage stress was compromised. Dealing with uncertain employment status exacerbated the economic challenges Latinas already faced prepandemic and resulted in the prioritization of living expenses and delaying health care. Participants were supportive of the idea of being offered more financial and stress management classes and support group discussions to help them navigate the challenges they face due to financial hardships. Conclusion: The study provides evidence from qualitative data analysis supporting the development of educational and coaching programs aimed at enhancing the mental health and financial well-being of LMI Latinas. Group or communal activities with peer support may prove effective alternatives and augment traditional mental health counseling.